PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN DENGAN POFITABILITAS SEBAGAI VARIABEL MODERASI (Studi Empiris Pada Perusahaan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Periode 2011-2015) - Ditha Restu Andini, 13.05.52.0026; Badjuri, Achmad (Students' Journal of Accounting and Banking, 2017)
The aim of this research are to testthe effect of CSR and GCG proxied by the independent board. The effect of profitability as the moderating variable in relations between CSR dan towards firm’s value. The sample was a mining company listed on the Stock Exchange period 2011-2015 by using purposive sampling. The analysis method of this research is multiple linear regression method. The result of research show that the effect CSR on firm’s value was negative significant. The effect of GCG proxied by the independent board on firm’s value was negative not significant. Profitability as the moderating variabel in relation between CSR and firm’s value was significant. Profitability as the moderating variabel in relation between GCG on firm’s value was not significant.Keywords: Corporate Social Responsibility, Good Corporate Governance, Firm Value, Profitability